Intrauterine ovarian torsion with autoamputation and intra-abdominal wandering mass: a report of three cases and literature review - Liu, Xinxing; Ding, Guojian; Tian, Wenchao; Liu, Xijie; Fu, Tingliang; Liu, Hongzhen; Xu, Aiqun; Han, Xinling; Feng, Wenyu; Geng, Lei (Frontiers in Medicine, 2025)
Intrauterine ovarian torsion with autoamputation (IOTA) in fetuses was uncommon. The vague and non-specific symptomatology of IOTA makes early diagnosis challenging. Potential complications, such as hemorrhagic infarction of the adnexal structures with the subsequent sequelae, may occur. Moreover, therapeutic options, such as conservative or surgical management, for IOTA remain uncertain in the literature. We report three cases of IOTA, two of which were complicated by peritoneal adhesion or spontaneous bacterial peritonitis, confirmed surgically and through laboratory studies. A suspected diagnosis of this uncommon condition was made preoperatively in two cases. Our case reports provided additional information about this rare condition, including the occurrence of complicated bacterial peritonitis, in neonates and infants with IOTA. A review of the literature on imaging diagnosis and management options for IOTA is also included.